The effects of play stimulation on cognitive capacities of chickens - Zeiträg, Claudia; Jensen, Per (Frontiers in Ethology, 2024)
Play is a widespread phenomenon in the animal kingdom with observations from all vertebrate classes. The adaptive value of this behaviour, however, remains unclear. In the past century, numerous theories have been put forward, ranging from releasing surplus energy to training species-specific behaviours. However, none of these theories can fully explain the functions of play. A recent neurocognitive theory suggests that play allows the brain to encounter many different and surprising situations that provide it with opportunities to learn about the environment and form predictions about it. This theory has, however, to our knowledge, previously not been experimentally tested. To start exploring the connection between play and cognition, we compared the cognitive capacities of White Leghorn chicks that were stimulated to play in the first five weeks of their lives with chicks that did not receive any play stimulation. More specifically, we wanted to test the connection between specific types of play and cognitive domains. To achieve this, we designed two play treatments: object players that were provided with a variety of toys during their treatment, and social players that were released into an arena with plenty of space and conspecifics, as this has previously been shown to trigger social play. Subsequently, all three treatments (control, object players, social players) were tested in a cognitive test battery consisting of two experiments targeting the social domain and two targeting the physical domain. We found no improvement of cognitive capacities in either play treatment group compared to control subjects, though the social play treatment appears to have affected some behavioural variables recorded during the cognitive tests. Chicks that had played socially were in general bolder, more explorative and had more access to resources in the tests. This might subsequently allow them to exploit their environment more efficiently, which could in turn affect their welfare as they might be more resilient to stress and have more access to resources. More studies will be needed to assess the long-term effects of play on cognitive capacities and welfare of chickens.